Public Sector Innovation Support by European States: Its Characteristics and Impact on Firms - Marta Orviská; Juraj Nemec (European Financial and Accounting Journal, 2015)
In this paper we are concerned with the impact the public sector has on private sector innovation. Perhaps the most important issue is whether public sector innovation, or lack of it, impacts upon private sector firms. But we are also concern the extent perceptions of innovation across jurisdictions and also the characteristics of firms, which benefit from public sector innovation. There is a particular focus on the role of the Internet. In doing this we make use of Eurobarometer data on firms and their attitudes to public sector innovation. We have established that firms benefit from public sector innovation. The factors, which impact on growth, include improvements due to Internet form filling and the reduction in the government's response time with respect to government services. The factors that impact on firm innovation, which may be tomorrow's growth, include the access to information on government services and also factors, which reduce costs.
Keywords: O31; 650; Innovations; Public sector; Private sector